2018
DOI: 10.1053/j.gastro.2018.01.044
|View full text |Cite
|
Sign up to set email alerts
|

HBV Bypasses the Innate Immune Response and Does Not Protect HCV From Antiviral Activity of Interferon

Abstract: In dHepaRGNTCP cells and PHHs, HBV evades the induction of IFN and IFN-induced antiviral effects. HBV infection does not rescue HCV from the IFN-mediated response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
121
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 136 publications
(132 citation statements)
references
References 74 publications
10
121
0
1
Order By: Relevance
“…reports (18,35), IFN-␣ slightly inhibited cccDNA formation and HBeAg secretion in a dose-dependent manner when administered at 1,000 IU/ml ( Fig. 10B and C).…”
Section: Kinetics Of Cccdna Establishment In In Vitro-infected Hepatomentioning
confidence: 88%
“…reports (18,35), IFN-␣ slightly inhibited cccDNA formation and HBeAg secretion in a dose-dependent manner when administered at 1,000 IU/ml ( Fig. 10B and C).…”
Section: Kinetics Of Cccdna Establishment In In Vitro-infected Hepatomentioning
confidence: 88%
“…Immunofluorescence was performed as described in [65]. For cholesterol staining, Filipin-III (250 µg/mL, Sigma-Aldrich) was used instead of a primary and secondary antibody.…”
Section: Immunofluorescence (If) Filipin Staining and Bright Field Mmentioning
confidence: 99%
“…The innate immune response is not sufficiently stimulated in the early stage of HBV infection to enable viral clearance. The findings in liver tissues of chimpanzees and CHB patients as well as experiments in vitro have shown that the endogenous IFNα and interferon‐stimulated genes (ISGs) were all not induced while HBV infection . Some research reported that the level of IFNα released by HBV‐infected PHH cells was even decreased and the expression of antiviral genes was hardly observed even in co‐culture with Kupffer cells (KC) …”
Section: Relationship Between Host and Hbvmentioning
confidence: 99%
“…The and interferon-stimulated genes (ISGs) were all not induced while HBV infection. 19,40 Some research reported that the level of IFNα released by HBV-infected PHH cells was even decreased and the expression of antiviral genes was hardly observed even in co-culture with Kupffer cells (KC). 41 HBV modulates immune cells function in order to favour its infection even its maintenance.…”
Section: Immune Cells and Cytokinesmentioning
confidence: 99%